MENENTUKAN JALUR TERPENDEK MENGGUNAKAN ALGORITMA A* DAN ALGORITMA FLOYD WARSHAL - Sarbaini Sarbaini; Ilham Dangu Rianjaya (MAp (Mathematics and Applications) Journal, 2023)
When graphs are used to solve the problem of determining the shortest route, it has become a common topic of discussion. Typically, these solutions are used to optimize aspects such as travel time. Using the Floyd-Warshall and A* algorithms, this research assists the community, particularly visitors, in determining the most sensible route from the Rimbo Panjang front gate to each building at UIN Suska Riau. The calculation technique is performed manually. The algorithm developed by Floyd Warshall yields more efficient calculation results. The results of calculations conducted by both algorithms are the same and have the correct minimum weight value. In a comparative analysis test, Warshall's algorithm is more efficient than the A* algorithm because it has a higher minimum weight that has been effectively tested for distance, trajectory, and distance. A comparison of the Floyd-Warshall algorithm and the A* algorithm reveals that the Floyd-Warshall algorithm determines the shortest route more effectively.